Cal State East Bay Magazine - CSUEB Office of University Communications & Marketing:::::: (2021)
The successor to Haywire, Cal State East Bay Magazine was published two or three times a year by the CSUEB Alumni Association and the CSUEB Office of University Advancement's Communications Department for alumni and friends of California State University, East Bay.